Biocompatibility evaluation of three different titanium-hydroxyapatite composites - (:unkn) unknown (Trans Tech Publications Ltd, 2005)
Titanium reinforced with hydroxyapatite (TiHA) prepared using 15% of titanium and 3 different sinterizing temperatures 1100, 1200 and 1300°C showed a significant increase in cell proliferation, when compared to the control.
Keywords: Alkaline phosphatase; Collagen; Hydroxyapatite; Osteoblasts; Titanium